Designing Dialogue Journal to Guide Teaching Practice Process through Online Tutorial at Universitas Terbuka - A. Andayani; Siti Julaeha (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
During this time, PGSD Program at UT provides the face-to-face tutorial (TTM) for practice courses such as the Strengthening of Teaching Skill (PKM). By reason of the students are spread far apart and the number is less, so it is inefficient to organize TTM for PKM. Therefore, in the year of 2017,Ã‚Â  it was conducted a trial of an online tutorial for PKM. Whereas the tutor manages the online tutorial activity from a distance, the supervisor guides the teaching practice activities of the students directly in the classroom. The challenges occur due to student failure in interpreting tutor direction, and uncontrolled validity of teaching practice process. To answer the challenge, a Dialogue Journal is designed, as an instrument that presents the validity of the supervision process. Through a descriptive method approach, it will be developed the pattern of online tutorial activities for PKM conducted by UT. In addition, some concepts of online dialogue and teaching supervision activities will be reviewed as well. Based on reviews of a document and the results of observation of the ongoing online tutorial, the hypothetical design of the dialog journal will be proposed as well as to be presented the pattern of the online tutorial with journal dialogue for PKM.Ã‚Â